Two new Byrathis species (Copepoda: Calanoida) from the deep South Atlantic and Southern Ocean and first description of an adult male - Markhaseva, Elena L.; Renz, Jasmin (Zootaxa, 2011)
Two new species, Byrathis divae sp. nov. and B. penicillatus sp. nov., are described from females collected in the deep waters and at abyssal depths above the sea bed, and are the first representatives of the genus recorded from the South Atlantic. Species of Byrathis Markhaseva & Ferrari, 2005 are divided into 2 groups. The first group, which includes both new species, contains medium sized copepods (from 2.1 to 4.9 mm) with a nude genital double somite, maxillule proximal basal endite with 3 setae, maxillule exopod with 6 or more setae, and maxilla endopod with 3 worm-like and 5 brush-like sensory setae. The second group contains small species (less than 1.4 mm) that share the surface ornamentation of the genital double somite, maxillule proximal basal endite with 2 setae, maxillule exopod with 5 setae or less, and maxilla endopod with 5 worm-like plus 3 brush-like sensory setae. For the first time an adult Byrathis male is described after Byrathis arnei Schulz, 2006 from the Southern Ocean. Among males of Clausocalanoidea that possess sensory setae on maxilla and maxilliped, the Byrathis male is well defined by symmetric antennules (ancestral segments XXII–XXIII fused on both sides) and poorly expressed P5 coxa and basis asymmetry, with both exopods 3-segmented and the right leg uniramous.